2023
DOI: 10.1038/s41537-022-00328-7
|View full text |Cite
|
Sign up to set email alerts
|

Progressive brain abnormalities in schizophrenia across different illness periods: a structural and functional MRI study

Abstract: Schizophrenia is a chronic brain disorder, and neuroimaging abnormalities have been reported in different stages of the illness for decades. However, when and how these brain abnormalities occur and evolve remains undetermined. We hypothesized structural and functional brain abnormalities progress throughout the illness course at different rates in schizophrenia. A total of 115 patients with schizophrenia were recruited and stratified into three groups of different illness periods: 5-year group (illness durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Several reasons may explain this finding. First, long DOI is associated with more severe alterations in brain structure and function in SCZ, 50,51 which is consistent with both the neurodevelopmental and neurodegenerative theories of SCZ 52,53 . For instance, a 10-year follow-up study found that patients with SCZ exhibited a progressive decline in intelligence and specific neurocognitive domains, including verbal knowledge and memory, following the onset of the illness.…”
Section: Effect Of Clinical Factorssupporting
confidence: 70%
“…Several reasons may explain this finding. First, long DOI is associated with more severe alterations in brain structure and function in SCZ, 50,51 which is consistent with both the neurodevelopmental and neurodegenerative theories of SCZ 52,53 . For instance, a 10-year follow-up study found that patients with SCZ exhibited a progressive decline in intelligence and specific neurocognitive domains, including verbal knowledge and memory, following the onset of the illness.…”
Section: Effect Of Clinical Factorssupporting
confidence: 70%
“…Nonetheless, schizophrenia patients have also been shown to have higher whole brain SC‐FC couplings (van den Heuvel et al, 2013 ). This disparity may result from the complex neurological disease pathways that are affected by variables such as the length of the illness (Shen et al, 2023 ) and the use of antipsychotic medications (Abbott et al, 2013 ). Variations may also be introduced by different approaches to aligning SC with FC, such as correlation‐based FC or precision‐based FC (Huang & Ding, 2015 ; Liégeois et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could result in internal dialogues being mistakenly identified as external, which would ground the symptoms seen in AVH and schizophrenia. Nonetheless, schizophrenia patients as the length of the illness (Shen et al, 2023) and the use of antipsychotic medications (Abbott et al, 2013). Variations may also be introduced by different approaches to aligning SC with FC, such as correlation-based FC or precision-based FC (Huang & Ding, 2015;Liégeois et al, 2020).…”
Section: The Relationship Between Changes In Sc-fc Coupling and Clini...mentioning
confidence: 99%
“…1 , 2 Clinical examination such as magnetic resonance imaging (MRI) has been found to be helpful and useful clinically for detecting the structure abnormalities in certain diseases, such as schizophrenia, the chronic brain disorder. 3 In addition, MRI has been developed and utilized for the texture analysis in discrimination of tumors in patients diagnosed with medulloblastoma. 4 In the work reported by Zheng et al, an MRI-based texture feature model was utilized to provide a new approach for noninvasive and preoperative identification of BRAF V600E mutation and to find the mutation location in the tissue.…”
Section: Dear Editormentioning
confidence: 99%